THE TRANSLATOR (AND THE) LEXICOGRAPHER - Consolin Dezotti, Maria Celeste [UNESP] (Univ Federal Santa Catarina, Nucleo Traducao, 2018)
Translation makes the interaction between two linguistic worlds, the source language and the target language. The use of dictionaries is indispensable for translating dead languages, such as latin and ancien greek. On the other hand, this interaction often benefits the target language, which incorporates new words. This approach focuses translations of greek texts into portuguese language. We consider dictionaries on two aspects: (I) as it is a guide to speak a language - and to its reception, especially in relation to dead languages -, in ancient greek dictionaries words and meanings are added whenever new texts are discovered; (II) the meanings' richness of some greek words encourages translators to transliterate them, and when they become usual, they can be included in a dictionary. This is possible because languages' lexicon is open. This statement is valid even if for a dead language.
Keywords: Translation; Dictionary; Ancient Greek; Lexicon; Lexicography